2017
DOI: 10.1104/pp.17.00709
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Basis of Plant Architecture in 10 Maize Recombinant Inbred Line Populations

Abstract: Plant architecture is a key factor affecting planting density and grain yield in maize (Zea mays). However, the genetic mechanisms underlying plant architecture in diverse genetic backgrounds have not been fully addressed. Here, we performed a large-scale phenotyping of 10 plant architecture-related traits and dissected the genetic loci controlling these traits in 10 recombinant inbred line populations derived from 14 diverse genetic backgrounds. Nearly 800 quantitative trait loci (QTLs) with major and minor e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 60 publications
5
81
0
Order By: Relevance
“…Our study sheds light on the genetic architecture of tocopherols in maize kernels. Tocopherol content is controlled by a few loci with major effects and a number of loci with minor effects, in contrast to the patterns for several other complex quantitative traits in the same genetic background (Liu et al, 2017;Pan et al, 2017;Xiao et al, 2016). Epistasis only plays a minor role, as reported by others (Liu et al, 2017;Pan et al, 2017;Xiao et al, 2016).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our study sheds light on the genetic architecture of tocopherols in maize kernels. Tocopherol content is controlled by a few loci with major effects and a number of loci with minor effects, in contrast to the patterns for several other complex quantitative traits in the same genetic background (Liu et al, 2017;Pan et al, 2017;Xiao et al, 2016). Epistasis only plays a minor role, as reported by others (Liu et al, 2017;Pan et al, 2017;Xiao et al, 2016).…”
Section: Discussionmentioning
confidence: 76%
“…Tocopherol content is controlled by a few loci with major effects and a number of loci with minor effects, in contrast to the patterns for several other complex quantitative traits in the same genetic background (Liu et al ., ; Pan et al ., ; Xiao et al ., ). Epistasis only plays a minor role, as reported by others (Liu et al ., ; Pan et al ., ; Xiao et al ., ). In terms of the allele frequency of the identified loci, minor alleles with a frequency of <0.1 were the favourable alleles for most of the significant loci identified.…”
Section: Discussionmentioning
confidence: 99%
“…Those traits have a highly polygenic genetic architecture that is mainly controlled by many small effect QTLs (Mickelson et al ; Peiffer et al ; Raihan et al ; Xu et al ). Parental phenotypic and genetic distances are positively associated with the effects and numbers of QTLs yielded (Pan et al ), and major‐effect QTLs can be more easily mapped to a higher resolution (Wang et al ). In our case, the phenotypic variation contribution rates were 26.7% ( q5‐F‐THFa ) and 14.9% ( q5‐F‐THFb ), respectively, reflecting that both are major‐effect QTLs.…”
Section: Discussionmentioning
confidence: 99%
“…To verify the accuracy of the QTL, we compared the previously reported QTLs and genes related to plant height and found that 45% of the QTLs overlapped with previous research (Peiffer et al, 2014; Yang et al, 2014; Dell’Acqua et al, 2015; Zhou et al, 2016; Pan et al, 2017). In addition, genes involving the GA and auxin pathway were also detected to be associated with plant height, such as ARFTF4 , D3 , GA2OX8 , KS3 , PIN1 and PIN11 , indicating that the QTL results of this study were highly reliable (Tudroszen et al, 1977; Winkler and Helentjaris,1995; Lo et al,2008; Yamaguchi, 2008; Li et al, 2016; Weijers et al, 2018).…”
Section: Resultsmentioning
confidence: 96%
“…Plant height was so important that people have made unremitting efforts to exploring its genetic mechanism. So far, there were plenty of quantitative trait loci (QTLs) identified for maize plant height using a diversity of genetic populations (Peiffer et al, 2014; Yang et al, 2014; Dell’Acqua et al, 2015; Zhou et al, 2016; Pan et al, 2017). Some of these genes were cloned, such as an1 , dwarf3 , dwarf8 , dwarf9 and br2 , which were mainly involved in the synthesis and transportation of gibberellin and auxin (Winkler and Freeling, 1994; Bensen et al, 1995; Winkler et al, 1995; Fujioka et al, 1988; Xing et al, 2012).…”
Section: Introductionmentioning
confidence: 99%